One mother for two species via obligate cross-species cloning in ants - Y. Juvé; C. Lutrat; A. Ha; A. Weyna; E. Lauroua; A. C. Afonso Silva; C. Roux; E. Schifani; C. Galkowski; C. Lebas; R. Allio; I. Stoyanov; et al. (Nature, 2025)
Abstract Living organisms are assumed to produce same-species offspring1,2. Here, we report a shift from this norm in Messor ibericus, an ant that lays individuals from two distinct species. In this life cycle, females must clone males of another species because they require their sperm to produce the worker caste. As a result, males from the same mother exhibit distinct genomes and morphologies, as they belong to species that diverged over 5 million years ago. The evolutionary history of this system appears as sexual parasitism3 that evolved into a natural case of cross-species cloning4,5, resulting in the maintenance of a male-only lineage cloned through distinct species’ ova. We term females exhibiting this reproductive mode as xenoparous, meaning they give birth to other species as part of their life cycle.